Uranyl-anchored MCM-41 as a highly efficient photocatalyst in the oxidative destruction of short chain linear alkanes: an in situ FTIR study - Krishna, Vidya; Kamble, Valmik S.; Gupta, Narendra M.; Selvam, Parasuraman (Journal of Physical Chemistry C, 2008)
Uranyl ions anchored in the mesopores of MCM-41 molecular sieve were found to be a highly efficient heterogeneous photocatalyst in the complete degradation of short chain linear alkanes such as methane, ethane, propane, and butane, carried out under ambient conditions of light irradiation. In addition to the formation of carbon dioxide and water, a negligible amount of methane was detected during the photooxidation of ethane, propane, and butane. Further, small amounts of ethane were also obtained during photooxidation of butane, suggesting quenching of *UO22+ by a C-C bond cleavage, in addition to a hydrogen atom abstraction. An C, in situ Fourier transform IR spectroscopy analysis was employed in order to monitor the photooxidation of methane and ethane over *UO22+/MCM-41, where formic acid, formaldehyde, and formate species were the transient species identified from methane, and acetic acid, acetaldehyde, and acetate species were the intermediates obtained from ethane. Appropriate reaction pathways were proposed based on the formation of these species (C-H cleavage) and also from the negligible quantitites of methane and ethane obtained during photooxidation of higher alkanes (C-C cleavage).